2020
DOI: 10.3390/w12113149
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Enabling Factors for Central and Household Level Water Treatment in a Refugee Setting: A Mixed-Method Study among Rohingyas in Cox’s Bazar, Bangladesh

Abstract: Water chlorination is widely used in emergency responses to reduce diarrheal diseases, although communities with no prior exposure to chlorinated drinking water can have low acceptability. To better inform water treatment interventions, the study explored acceptability, barriers, and motivating-factors of a piped water chlorination program, and household level chlorine-tablet distribution, in place for four months in Rohingya refugee camps, Cox’s Bazar, Bangladesh. We collected data from June to August 2018 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Recently, it was reported that water sources in FDMN-camps were unevenly distributed. Many people walk long distances through densely inhabited camps after collecting water (30,31), providing opportunity for contamination due to unsafe handling during transport. Furthermore, household storage containers in humanitarian settings often had observed faecal contamination likely due to insu cient regular cleaning (32).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that water sources in FDMN-camps were unevenly distributed. Many people walk long distances through densely inhabited camps after collecting water (30,31), providing opportunity for contamination due to unsafe handling during transport. Furthermore, household storage containers in humanitarian settings often had observed faecal contamination likely due to insu cient regular cleaning (32).…”
Section: Discussionmentioning
confidence: 99%
“…One of the investigators (NA), along with the field research team, conducted initial scoping visits to the selected camps and performed preliminary water quality assessments measuring iron, turbidity, and total dissolved solids (TDS) using digital field-test kits. We selected four underground shallow tubewells (less than 76 m) from the selected Camps [ 14 ] with different water physicochemical properties (tubewell ID-13 and tubewell ID-17 from Camp 1 and tubewell ID-2 and tubewell ID-5 from Camp 2) and based on the following eligibility criteria: (1) water point shared by 90–100 households, (2) water extracted by a manual underground shallow tubewell, (3) the tubewells were the primary drinking water source for the families/users, and (4) had sufficient space around the platform of the tubewell for Zimba installation.…”
Section: Methodsmentioning
confidence: 99%
“…Point-of-use (POU) chlorination is common in humanitarian settings due to the availability of chlorine products, ease of use, cost-effectiveness, efficacy in inactivating viral and bacterial pathogens, and maintenance of residual chlorine in treated water that protects against recontamination during storage [ 12 ]. However, regardless of substantial benefits, several studies revealed that successful chlorination programs in humanitarian settings are challenging owing to several reasons [ 13 , 14 , 15 , 16 , 17 ]. Previous studies from Bangladesh suggested that the taste and smell of chlorine in water, the time required for daily water treatment, personal motivation, knowledge, and behavior change are considerable barriers to POU treatment uptake, resulting in inconsistent and inaccurate practices [ 14 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations